The Spiritual Traditions of the Banyumas Community as a Representation of Magical Realism in Ahmad Tohari's Novel "Ronggeng Dukuh Paruk" - Hanannya Hana; Jamila Wijayanti (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2025)
This study aims to describe the representation of magical realism in the novel Ronggeng Dukuh Paruk using Wendy B. Faris's theory of characteristics through a qualitative descriptive method. The results confirm five main characteristics: the belief of the Banyumas community that ronggeng are possessed by indang (an inseparable element); spiritual respect in cungkup (the phenomenal world); Srintil's loss of identity due to the pressure of the traditions of Dukuh Paruk Village, creating unresolved doubts; the merging of the real and supernatural worlds; and the disruption of space, time, and identity, such as non-linear narratives, the blurred space of Nyai Kartareja, and Srintil's dualistic transformation. This reflects the spiritual traditions of Banyumas in Indonesian literature. The findings regarding the representation of magical realism contained in Ahmad Tohari's novel Ronggeng Dukuh Paruk can be used as a reference for future researchers in the field of literary sociology, particularly in the discourse of magical realism. As for the benefits for readers, it can broaden their knowledge and understanding of magical realism in a spiritual tradition.